Two new species of Microlepia (Dennstaedtiaceae, Polypodiopsida) from Thailand - Wang, Jenn-Che; Chang, Yi-Han; Chiou, Wen-Liang; Liu, Ho-Yih (Phytotaxa, 2017)
After examining the specimens of genus Microlepia in some major herbaria for the purpose of monographic study, two new species, namely Microlepia kerrii, and M. thailandensis, are recognized and described with photographs of type specimens herein.